The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1634/theoncologist.2017-0541
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival Rates of Patients with Stage III–IV Hodgkin Lymphoma According to Age, Sex, Race, and Socioeconomic Status, 1984–2013

Abstract: Long-term survival rates of patients with advanced Hodgkin lymphoma were elaborated in this article. The disparities according to sex, race, and socioeconomic status of survival condition were analyzed and showed the development of the public health care system and modern medicine technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
9
1
Order By: Relevance
“…A study by Shenoy et al also demonstrated an improvement in the survival of HL over time but included both early‐ and advanced‐stage HL as well as nodular lymphocyte predominant HL . Another study by Li et al, focusing on patients with advanced‐stage HL from the SEER database, demonstrated improving survival from 1983 to 2013 . However, there are key differences between this study and our study.…”
Section: Discussioncontrasting
confidence: 55%
“…A study by Shenoy et al also demonstrated an improvement in the survival of HL over time but included both early‐ and advanced‐stage HL as well as nodular lymphocyte predominant HL . Another study by Li et al, focusing on patients with advanced‐stage HL from the SEER database, demonstrated improving survival from 1983 to 2013 . However, there are key differences between this study and our study.…”
Section: Discussioncontrasting
confidence: 55%
“…We only adjusted the excess mortality estimates for age and year of diagnosis, but cancer survival is affected by multiple, interacting factors such as disease stage, tumor characteristics, treatment and ability to tolerate and comply to treatment, comorbidity burden, performance status, socioeconomic status, and more. In studies including detailed prognostic factors, male sex has remained a significant negative prognostic factor in several lymphoma subtypes 13,14,16,17,32–41 . In a large UK study that explored the effect of comorbidity and socioeconomic factors on DLBCL and FL survival, male sex was an independent, negative prognostic factor in both subtypes despite meticulous adjustments 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant survival disadvantage in men compared to women with cHL. Male sex is included in the IPS 11 and has remained a consistent negative prognostic factor in recent studies, 9,12,13 although some studies have suggested a weakened association over time 38,45,46 . Interestingly, cHL subclass distribution differs between men and women, 12 suggesting sex‐related differences in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 , 35 Similarly, AYAs are likely to be under‐insured and this, in conjunction with socioeconomic status and geographic factors may contribute to their treatment locations, which in turn, likely impacts likelihood of CTT enrollment. 25 , 36 Further, health insurance status and socioeconomic status (SES) are both significantly associated with survival in AYAs with cancer, suggesting differences in the type and quality of care low‐income patients may be receiving across the U.S. 37 , 38 , 39 Numerous studies have shown that treatment at large academic centers is associated with improved survival rates for AYAs with cancer. One possible factor contributing to these findings related to location‐of‐care may be a difference in clinical trial enrollment rates across community and academic centers.…”
Section: Discussionmentioning
confidence: 99%